Mini-CEX Sebagai Metode Penilaian Keterampilan Klinis Mahasiswa Program Pendidikan Kepaniteraan Klinik Fakultas Kedokteran Universitas Gadjah Mada - Studi Pendahuluan - Reza M. Munandar; Yoyo Suhoyo; Tridjoko Hadianto (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2012)
Background: Mini-CEX was developed to assess clinical skills by direct observation. Mini-CEX as a clinical skills assessment tool had to fulfill four requirements: validity, reliability, effects on students, and practicality. The purpose of this study is to understand validity, reliability, and feasibility of Mini-CEX as a clinical skills assessment tool in medical core clerkship program at Faculty of Medicine Universitas Gadjah Mada.Method: Seventy four clerkship students from Internal Medicine and 42 clerkship students from Neurology Department were asked to do an observed Mini-CEX encounter for minimum amount of four in Internal Medicine and two in Neurology Department in the period of September 2010 to January 2011. The validity was analyzed with Kruskal-Wallis method for Internal Medicine, and Mann-Whitney Method for neurology Department, reliability was analyzed based on G coefficient, and feasibility was analyzed using descriptive statistic.Results: Mini-CEX’s validity is shown by p < 0,001 in Internal Medicine and p = 0,250 in Neurology Department, G coefficient for Internal Medicine and Neurology Department is 0,98 and 0,61 respectively. Feasibility in Internal Medicine and Neurology Department is 79,7 % and 100% respectively.Conclusion: Mini-CEX is valid and reliable in Internal Medicine but not in Neurology Department. Feasibility is good for both Internal Medicine and Neurology Department.